Retrospective study of ovarian malignancy managed in surgical unit at Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore - Shalla Imdad Ali; Raza Hasnain Sayyed; Sana Amir Akbar; Muhammad Abubakar; Aamir Ali Syed (Journal of the Pakistan Medical Association, 2020)
Objective: To determine the oncological outcome and pattern of ovarian tumour in patients who underwent surgical management. Methods: The retrospective, descriptive hospital-based study was conducted at Shaukat Khanum Memorial Cancer Hospital, Lahore, Pakistan, and comprised data of all patients who underwent surgical intervention for ovarian cancer between January 2010 and December 2015. Data was retrieved from the hospital database and analysed using SPSS 20. Results: Of the 236 patients, 203(86%) had undergone open surgery, while 33(14%) had had laparoscopic surgery. Neo-adjuvant chemotherapy was given in 60(25.42%) cases and adjuvant chemotherapy in 102(43.22%). Epithelial ovarian cancer in 201(85.16%) cases was the most common tumour type. Mortality was recorded in 36(15.5%) cases, while 41(19.9%) were lost to follow-up. Conclusion: Ovarian tumours were found to be difficult to treat and were associated with frequent recurrence. Key Words: Ovarian malignancy, Surgical management of ovarian cancer, Staging of ovarian cancer. Continuous...